Combined vaccines in the national prevention immunization schedules for the children in Belarus, Kazakhstan, Russia and Ukraine - A.A. Baranov; A.V. Gorelov; V.I. Zadorozhnaya; R.S. Idrisova; V.A. Matveev; L.S. Namazova; A.E. Platonov; T.S. Selezneva; V.K. Tatochenko; A.F. Frolov; O.V. Shamsheva (Педиатрическая фармакология)
Еhe announcement of the east European expert group for vaccine prevention presents position of the leading specialists of Russia, Belarus, Ukraine and Kazakhstan on key issues of the national pre vention immunization schedule. the authors examine in detail the aspects of vaccination against hepatitis type b, including optimal term of injection of the first vaccine dose, vaccination tactics for the premature and low weight newborns, safety of recombinant vaccines against hepatitis type в. based on the analysis of the morbidity of h. influenzae type b invasive forms along with the methods recommended by who (HIB RAT), experts recommend introduction of the vaccine against this infection into the prevention immunization schedule. The experts believe the basis for the combined vaccines in pediatrics to be the vaccines with cellfree pertussis component. This class of vaccines allows introducing the additional booster dose of pertussis vaccines for immunization of the preschool children into the immunization schedule, which is dictated by the present epidemic situation with due account for this infection. The experts note the importance of application of the combined vaccines in pediatrics, whose wide implementation into healthcare system practices is in the interests of the parents, medical officers and society.Key words: hepatitis type в, h. influenzae type b, HIB RAT, pertussis, diphteria and tetanus toxoids and pertussis vaccine, poliovaccines, combined vaccines, prevention immunization schedule, children.